"Łzami by tu pisać potrzeba" : leksykalne właściwości stylu polskiej dydaktyki wierszowanej czasów oświecenia - Maćkowiak, Krzysztof (1963- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The data collected in this book do not give an all-embracing panorama of the structure of formal versified didactic of Polish Enlightenment, even on the level of lexical shape, which the author already mentions in the introduction. One might discuss the choice of analyzed texts, and for some readers another comroversial issue would be the selection of certain verbal layers presented in the following chapters. However, it is impossible to avoid such problems in works aspiring to be synthesizing undertakings. The wider the scope of observation, the more marked contours of the panorama must be.
Keywords: język polski - stylistyka - 18 w.; język polski - słownictwo - 18 w.; poezja polska - 18 w.; stylistyka; literatura oświecenia; literatura parenetyczna; 18 w.